EFFECT OF PURPLE SWEET POTATO (Ipomoea batatas) EXTRACT AND FERMENTATION TIME IN WATER KEFIR CHEMICAL PROPERTIES - Latifa Putri Aulia; Sarah Febrian Perdaningtyas; Titia Muflihah; Tanalyna Hasna (Fakultas Teknologi Pertanian Universitas Brawijaya, 2022)
As a bacteria starter, water kefir is commonly made from water, sugar, dried or fresh fruits, and kefir grains. Purple sweet potato (PSP) contains natural anthocyanins and carbohydrates as colouring agents and carbon sources in water kefir drinks production. This study determines the effect of the PSP extract addition, fermentation time, and their interaction in the water kefir. The study was based on chemical properties such as total anthocyanins, antioxidant activity IC50, total acid, total sugar, degree of acidity (pH), and total dissolved solids (TDS). The method used Factorial Randomized Group Design with 0%, 10%, 30%, and 50% (v/v) of addition of PSP extract and 0, 24, and 48 hours of fermentation time as factors. The results were analyzed using Analysis of Variance (ANOVA) with a 5% confidence interval. The results showed that PSP extract addition and fermentation time significantly affected all chemical properties analysis and their interaction. The best treatment was retrieved with 50% PSP extract addition and 48 hours of fermentation time with total anthocyanin 193.197 ± 3.255 ppm, antioxidant activity IC50 460.620 ± 20.973 ppm, total acid 10.429 ± 0.371%, total sugar 1.356 ± 0.058%, pH 2.3 ± 0.058, and TDS 2.1 ± 0.2 ºBrix